Customer engagement design during the COVID 19 pandemic, mutual trust and intelligent automation: A conceptual perspective - Abdullah Abdulmohsen Alfalih (Journal of Innovation and Entrepreneurship, 2022)
The adoption and use of artificial intelligence, and the application of this concept through the development and implementation of intelligent automation is not considered simply as an option, but rather as an obligation in current times, due to the considerable change caused by the COVID 19 pandemic and responses to it. This study is an attempt to more thoroughly understand and clarify how the adoption of such intelligent automation can work to improve customer engagement in the food and restaurant domain. To attend to this objective, a theoretical framework is developed and tested based on an integrative approach of determinants of customer engagement through artificial intelligence to increase trust levels when intelligent automation is used. This paper will contribute to the construction of a matrix of customer engagement based on the different steps identified in the customer engagement cycle, and build a co-constructive and dynamic model of customer engagement in relation to mutual' trust and intelligent automation.
Keywords: 650; Artificial intelligence (AI); Co-construction; Customer engagement (CE); Intelligent automation (IA); Mutual trust